Ludwig Jekels papers - Jekels, Ludwig, 1867-1954.; Silberer, Herbert, 1882-1922.
Correspondence, lectures, subject files, and writings relating to Jekels's work on dreams, sleep, and wakefulness. Includes Paul Federn's response to one of Jekels's writings; autograph book containing the signatures of Thomas Mann and others relating to Mann's lecture, "Freud und die Zukunft," given at a banquet honoring Sigmund Freud (May 1936); and correspondence and writings of Herbert Silberer (1919-1922). Correspondents include August Aichhorn, Princess Marie Bonaparte, K.R. Eissler, Thomas Mann, Otto Rank, and Gregory Zilboorg.
Psychoanalyst. Changed name from Jekeles in 1903; immigrated to the U.S. in 1938.
Collection material in German and English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Originally processed as part of the Sigmund Freud Papers from which it was separated in 1990.
Keywords: Aichhorn, August, -- 1878-1949 -- Correspondence; Bonaparte, Marie, -- Princess, -- 1882-1962 -- Correspondence; Eissler, K. R. -- 1908-1999 -- Correspondence; Federn, Paul; Freud, Sigmund, -- 1856-1939.; Mann, Thomas, -- 1875-1955 -- Correspondence; Rank, Otto, -- 1884-1939 -- Correspondence; Zilboorg, Gregory, -- 1890-1959 -- Correspondence; Dreams; Psychoanalysis; Sleep; Wakefulness; Psychoanalysts